THE MYTH OF ‘ABŪ LAHAB’ IN Q.S. AL-MASAD [111]: 1: ANALYSIS OF ROLAND BARTHES’ SEMIOTIC THEORY - Syafirin, Muhammad (Sekolah Tinggi Agama Islam Sadra, 2024)
The Qur’anic story of “Abū Lahab” is often misunderstood by some who assume that the story is factual-exclusive. This article is designed to examine how the concept of Abū Lahab is understood in Qur’anic terms, and how it is embodied in today’s context. This research uses a library research method with a descriptive-analytical pattern, through Roland Barthes’ semiotic approach as a theoretical basis. Barthes argues that the language system can be understood through two steps of semiotic reading, the first is what he calls the linguistic system (language-object), and the second is the mythical system (metalanguage). To arrive at the mythical system, it is necessary to extract meaning through the signifier system, which consists of three elements: the signifier element, the signified element, and the sign element in the second layer of the semiotic system. Through Roland Barthes’ semiotic reading, the concept of Abū Lahab that is understood to be exclusively addressed to ‘Abd al-‘Uzzā is a myth. Abū Lahab is not a personal name, but a general and universal title. ‘Abd al-‘Uzzā is only one historical representation of the figure of Abū Lahab. From Barthes’ semiotics, Abū Lahab is more accurately understood as ‘anyone who opposes the truth and is intolerant (radical) towards other groups, not hesitating to carry out offensive resistance to them if it is not in line with their personal or group ideology or political interests’. Thus, in the modern context, anyone can potentially become “Abū Lahab” as the khiṭab of Q.S. Al-Masad if they share these characteristics.